ChemInform Abstract: Enantioenriched β‐Lactone and Aldol‐Type Products from Regiodivergent Carbonylation of Racemic cis‐Epoxides. Issue 41 (7th October 2014) - Mulzer, Michael; Ellis, W. Chadwick; Lobkovsky, Emil B.; Coates, Geoffrey W.
Abstract The new catalytic system is also applied to the synthesis of compound (VIII) which is a key fragment of the antibiotic globomycin.